2019
DOI: 10.1186/s12934-019-1141-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the xylose paradox in Saccharomyces cerevisiae through in vivo sugar signalomics of targeted deletants

Abstract: Background There have been many successful strategies to implement xylose metabolism in Saccharomyces cerevisiae , but no effort has so far enabled xylose utilization at rates comparable to that of glucose (the preferred sugar of this yeast). Many studies have pointed towards the engineered yeast not sensing that xylose is a fermentable carbon source despite growing and fermenting on it, which is paradoxical. We have previously used fluorescent biosensor strains to in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 84 publications
(143 reference statements)
1
37
0
Order By: Relevance
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz‐Ruiz, Rigoulet, & Devin, ) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, ). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, ; Brink, Borgström, Tueros, & Gorwa‐Grauslund, ; Jin et al, ; Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa‐Grauslund, ; Osiro et al, ). Considering that the isobutanol production pathway in SR8‐Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz‐Ruiz, Rigoulet, & Devin, ) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, ). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, ; Brink, Borgström, Tueros, & Gorwa‐Grauslund, ; Jin et al, ; Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa‐Grauslund, ; Osiro et al, ). Considering that the isobutanol production pathway in SR8‐Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz-Ruiz, Rigoulet, & Devin, 2011) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, 2002). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, 2003;Brink, Borgström, Tueros, & Gorwa-Grauslund, 2016;Jin et al, 2004;Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa-Grauslund, 2019;Osiro et al, 2018).…”
mentioning
confidence: 99%
“…Although there have been a number of successful strategies to implement xylose metabolism in S. cerevisiae , their efficiency so far has not been comparable to that of glucose [ 10 , 18 ]. Xylose paradox is a paradoxical phenomenon in the engineered yeast that do not sense xylose as a fermentable carbon source despite being able to grow on and ferment xylose [ 29 ]. Many studies showed that high xylose concentrations would trigger cellular signals similar to those generated due to low glucose concentrations, resulting in a starvation response rather than a fermentation response [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xylose paradox is a paradoxical phenomenon in the engineered yeast that do not sense xylose as a fermentable carbon source despite being able to grow on and ferment xylose [ 29 ]. Many studies showed that high xylose concentrations would trigger cellular signals similar to those generated due to low glucose concentrations, resulting in a starvation response rather than a fermentation response [ 29 , 30 ]. The results of the current study support the notion of xylose paradox and associated cellular signaling pathways, involving GCR2 as a metabolic regulator.…”
Section: Discussionmentioning
confidence: 99%
“…0.1 g PirXI per g biomass estimated based on on 25% of the total protein being XI, and a total protein content of 0.4 g per g biomass [46,47]), V max (8.3 U/mg, from k cat = 6.9 s −1 with Mn 2+ ) and K M (6.2 mM) have their usual meaning. Y represents the yield on xylose (0.25 g cell dry weight/g xylose converted) estimated from a previous study performed with S. cerevisiae grown in a similar condition [48]. This predicts a PirXI activity at [S] = 1-10 mM (reasonable intracellular substrate concentration) [49,50] of 1-4.6 g xylose converted per g biomass per h, [6,51].…”
Section: Introduction Of Efficient Enzymes For Initial Isomerization mentioning
confidence: 99%